Volume 3: 30th Computers and Information in Engineering Conference, Parts a and B 2010
DOI: 10.1115/detc2010-28438
|View full text |Cite
|
Sign up to set email alerts
|

APU FMEA Validation and Its Application to Fault Identification

Abstract: FMEA (Failure Mode and Effects Analysis) is a systematic method to characterize product and process problems. As a standard document, an FMEA is produced during the design of a product or system. However, once a system is deployed, the corresponding FMEA is rarely validated and updated. This is mainly due to the lack of method to validate and update FMEA. This paper argues that historical maintenance and operational data could be used to help address this problem. Building on data mining and database technique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…The last four columns show the revised information which closely reflects the real maintenance practice. For the original information, please refer to [3]. We added the ranking information based on RPN.…”
Section: Overview Of the Fmea V Altdationmentioning
confidence: 99%
See 2 more Smart Citations
“…The last four columns show the revised information which closely reflects the real maintenance practice. For the original information, please refer to [3]. We added the ranking information based on RPN.…”
Section: Overview Of the Fmea V Altdationmentioning
confidence: 99%
“…We strongly suggested that prior to use FMEA information, one must try to confirm its validity. In our previous work [3,4], we had performed this task using real-world readily available maintenance and operational data. In particular, we had investigated validation and updating of an FMEA for an APU (Auxiliary Power Unit engine).…”
Section: Overview Of the Fmea V Altdationmentioning
confidence: 99%
See 1 more Smart Citation
“…The [53] presented the APU failure mode and effect analysis. Through an investigation of maintenance records, the paper validated all the possible component faults that can lead to the "APU inability to start" failure effect.…”
Section: Objectivesmentioning
confidence: 99%
“…Failing to start the APU is extremely dangerous for an aircraft during a flight, when engines need a restart. Starter failure has been identified as the primary reason for the APU starting failures [11], [12]. A starter failure can also cause operational interruptions with escalated maintenance costs.…”
Section: List Of Tablesmentioning
confidence: 99%